An intervention study of the general practice management of older adults with cardiovascular metabolic comorbidities - Yunjing Li; Zhehua Zou; Shuangyan Yi; Yue Yang; Guanli Yuan; Jingping Xu (PLoS ONE, 2026)
Purpose To investigate the impact of general practice management on treatment compliance, lifestyle, and clinical indicators in older adults with cardiovascular metabolic comorbidities to provide more effective disease management strategies for this population. Patients and methods This randomized controlled trial enrolled 200 older adults with type 2 diabetes and established atherosclerotic cardiovascular disease (e.g., coronary heart disease, ischemic stroke) who were discharged from Qinhuangdao First Hospital between November 2021 and May 2023. Patients were randomly divided into intervention and control groups (n = 100 per group). The intervention group received general medical management, including personalized health education during hospitalization, community outpatient follow-up after discharge, and lifestyle interventions. The control group received routine discharge guidance. Changes in medication usage, body mass index (BMI), smoking rate, and clinical indicators, such as glycated hemoglobin, low-density lipoprotein cholesterol, and creatinine levels were evaluated over a 12-month follow-up period. Dietary intake and physical activity were assessed using the Semi-Quantitative Food Frequency Survey Questionnaire and the Physical Activity Scale for the Elderly, respectively. Results After 12 months, 91 controls and 95 intervention patients remained and were analyzed per-protocol. Within-group analyses revealed that the intervention group successfully maintained high utilization rates of all recommended medications (metformin, SGLT2i, GLP-1RA, aspirin/clopidogrel, statins, ACEI/ARB), whereas the control group experienced significant declines (all P < 0.05). Both groups achieved significant reductions in BMI, but only the intervention group showed a significant decrease in smoking rates (P = 0.014). The intervention group demonstrated comprehensive dietary improvements (e.g., increased nuts, dairy, vegetables, and aquatic products; reduced refined carbohydrates, meats, and salt) and significantly increased physical activity scores (all P < 0.05). Clinically, while both groups achieved reductions in glycated hemoglobin and LDL-C, only the intervention group showed significant improvements in creatinine levels, whereas renal function in the control group significantly deteriorated (P < 0.001). Conclusion A structured general practice management model effectively sustains long-term medication adherence, promotes comprehensive healthy lifestyle modifications, and optimizes key metabolic and renal clinical indicators in older adults with cardiovascular metabolic comorbidities. Trial registration Chinese Clinical Trial Registry ChiCTR2500112212.